(untitled) (Training and Practice : Journal of Educational Sciences, 2010)
The study deals with the training to be reader with practical opportunities. Last year the author examined pupils’ reading habits with the help of a survey. Taking into account the reuslts of the examination she conducted among primary school teachers, with which she wanted to know the valid methods and procedures in readers’ training. This study is the summary of these experiences.